2008
DOI: 10.1097/rlu.0b013e3181813096
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Pheochromocytomas in a Patient With Blurred Vision

Abstract: We report on a 19-year-old male diagnosed with multiple pheochromocytomas after an I-123 metaiodobenzylguanidine (MIBG) scan. Multiple imaging was obtained because of concern for von Hippel-Lindau disease (VHL) after bilateral retinal angiomas were discovered on ophthalmologic consultation as a follow-up from the Emergency Department. Computed tomography (CT) and magnetic resonance imaging (MRI) were able to localize the adrenal and extra-adrenal tumors; however, accurate differentiation between pheochromocyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Recurrence of bilateral pheochromocytoma was determined with I-123 MIBG scan in that case. Thoren et al (7) reported a case with multiple pheochromocytomas and VHLS. They performed I-123 MIBG before surgery to confirm that the lesions were indeed pheochromocytoma and to rule out any metastatic disease.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Recurrence of bilateral pheochromocytoma was determined with I-123 MIBG scan in that case. Thoren et al (7) reported a case with multiple pheochromocytomas and VHLS. They performed I-123 MIBG before surgery to confirm that the lesions were indeed pheochromocytoma and to rule out any metastatic disease.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…[18] Iodine-123 MIBG has been reported to diagnose multiple pheochromocytomas in VHL disease presenting initially with retinal angiomatosis. [19]…”
Section: Discussionmentioning
confidence: 99%
“…The use of MIBG scintigraphy in a woman with VHL has changed fundamentally her management, as presented in an older case report, when scintigraphy indicated a metastatic PHEO in a lesion initially considered to be a brainstem hemangioblastoma ( 27 ); PHEO metastases were seen with 123 I-MIBG in another case report ( 28 ). However, subjects with VHL have lower VMATs expression in chromaffin tissue, possibly hampering the use of MIBG as an effective functional imaging agent ( 29 , 30 ).…”
Section: Functional Imaging In Patients With Vhlmentioning
confidence: 99%